2008
DOI: 10.1007/s00011-008-8067-9
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin inhibits IgE-mediated histamine release by human basophils and Syk kinase activity

Abstract: These results indicate that the inhibition of Syk-dependent phosphorylation events might underlie the blocked histamine release from human basophils, thus contributing to the anti-inflammatory effects of shikonin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
3
13
0
3
Order By: Relevance
“…The presence of shikonin caused a small increase in the average fiber diameter, but it did not affect their morphology, since their surface was also smooth as previously described (Taepaiboon et al, 2007;Tungprapa et al, 2007). Additionally, increasing the drug loading did not cause a significant effect on the mean fiber size, although it is a common effect of the drug loading, as reported elsewhere (Deitzel et al, 2001;Puppi et al, 2010;Takano-Ohmuro et al, 2008).…”
Section: Shikonin-loaded Fiberssupporting
confidence: 64%
“…The presence of shikonin caused a small increase in the average fiber diameter, but it did not affect their morphology, since their surface was also smooth as previously described (Taepaiboon et al, 2007;Tungprapa et al, 2007). Additionally, increasing the drug loading did not cause a significant effect on the mean fiber size, although it is a common effect of the drug loading, as reported elsewhere (Deitzel et al, 2001;Puppi et al, 2010;Takano-Ohmuro et al, 2008).…”
Section: Shikonin-loaded Fiberssupporting
confidence: 64%
“…Shikonin might be used in the treatment of asthma. Takano-Ohmuro et al (2008) has explored the use of shikonin in asthma by focusing on its anti-inflammatory activity (Takano-Ohmuro et al, 2008). Other investigators have used a mouse asthma model to demonstrate that shikonin inhibits bone marrow-derived dendritic cell maturation in vitro , and allergic action as well as tracheal hyperresponsiveness in vivo (Lee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Shikonin, one of the main active components of Zi Cao, has been shown to exert anti-inflammatory and anti-cancer effects both in vitro and in vivo (Wang et al, 1994; Yang et al, 2009a). Several molecular targets of shikonin have also been proposed (Wang et al, 1994; Staniforth et al, 2004; Nam et al, 2008; Su et al, 2008; Takano-Ohmuro et al, 2008; Yang et al, 2009a). We also reported that the proteasome is one of the important molecular targets of shikonin (Yang et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%